Respuesta :

Step-by-step explanation:

log10(18) = log10(2×3×3) = a

log10(24) = log10(2×2×2×3) = b

the rules of the logarithm :

logc(m×n) = logc(m) + logc(n)

log10(18) = log10(2) + log10(3) + log10(3) = a

log10(2) + 2×log10(3) = a

log10(24) = log10(2) + log10(2) + log10(2) + log10(3) = b

3×log10(2) + log10(3) = b

log10(2) = a - 2×log10(3)

using this in the b equation :

3×(a - 2×log10(3)) + log10(3) = b

3a - 6×log10(3) + log10(3) = b

3a - 5×log10(3) = b

-5×log10(3) = b - 3a

log10(3) = -(b - 3a)/5 = (3a - b)/5

similarly, from the b equation we get :

log10(3) = b - 3×log10(2)

and we use that in the original a equation :

log10(2) + 2×(b - 3×log10(2)) = a

log10(2) + 2b - 6×log10(2) = a

2b - 5×log10(2) = a

-5×log10(2) = a - 2b

log10(2) = -(a - 2b)/5 = (2b - a)/5